Study of the process of sublimation-dissociation of Ge3N4 - Irakli Nakhutsrishvili (Journal of Chemistry Letters)
The question of dissociation-sublimation of germanium nitride is considered. In the temperature range of 650-750oC it sublimates. In the range of ~(750–850)oC, partial dissociation of Ge3N4 is observed, which is accompanied by evaporation of the remainder of the solid phase. About 850oC and above Ge3N4 completely dissociates. The activation energies of the sublimation and dissociation processes were calculated from the temperature dependences of the sublimation rate and the dissociation rate constant. Their values were: Eact.(subl.)~255 kJ/mol and Eact.(diss.)~420 kJ/mol. During sublimation of crystalline germanium nitride in the cold zone of the reactor, an amorphous film is obtained. The film is germanium oxynitride (Ge3N4-xO1.5x) with a statistical distribution of nitrogen and oxygen atoms in the structural network of the material. According to our preliminary data, there is a possibility of controlling the sign and charge density at the Ge3N4-xO1.5x/Si interface. In this way it is possible to implement Metal-Dielectric-Semiconductor transistors of “normally open” and “normally closed” types.